“Improving Patient Outcomes with Chat bot Technology” (International Journal of Food and Nutritional Sciences, 2023)
Machine learning (ML) and artificial intelligence (AI) are now pervasive in our lives. There are several cutting-edge gadgets that will make our life easier and more convenient. The technology behind virtual assistants like chat bots is improving in this regard. A chat bot may be able to accurately diagnose a user's problem based on their replies; while in the past assistants were confined to a small set of frequently asked questions (FAQs). A large and accurate database of medical diseases and their symptoms will be used to train the algorithm. The proposed model uses a decision tree approach to assess the patient's complexity and provide a result. In response to the user's inquiries, a desired and highly accurate diagnosis is created. Machine learning (ML) and artificial intelligence (AI) are two technologies that are quickly developing and finding widespread use in modern society.